Delivery of climate services through Rwanda’s national agricultural extension service extended to 106,000 farmers, and deepened through climate service Radio Listening Clubs - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
Rwanda Climate Services for Agriculture supported the Twigire Muhinzi agricultural extension service to scale up Participatory Integrated Climate Services for Agriculture (PICSA) in 27 of Rwanda’s 30 districts, facilitating 106,000 Rwandan farmers to understand and act on climate information. Climate service delivery was deepened through the launch of 225 Radio Listening Clubs that convene PICSA participant farmers to listen to and discuss biweekly climate services radio broadcasts, take turns participating in call-in shows, and provide input to future programming content.